Transcription-associated recombination is independent of XRCC2 and mechanistically separate from homology-directed DNA double-strand break repair - Savolainen, Linda (Oxford University Press, 2009)
It has previously been shown that transcription greatly enhances recombination in mammalian cells. However, the proteins involved in catalysing this process and the recombination pathways involved in transcription-associated recombination (TAR) are still unknown. It is well established that both the BRCA2 protein and the RAD51 paralog protein XRCC2 are required for homologous recombination. Here, we show that the BRCA2 protein is also required for TAR, while the XRCC2 protein is not involved. Expression of the XRCC2 gene in XRCC2 mutated irs1 cells restores the defect in homologous recombination repair of an I-SceI-induced DNA double-strand break, while TAR is unaffected. Interestingly, the XRCC2-deficient irs1 cells are also proficient in recombination induced at slowed replication forks, suggesting that TAR is mechanistically linked with this recombination pathway. In conclusion, we show that TAR depends on BRCA2 but is independent of XRCC2, and that this recombination pathway is separate from that used to repair a two-ended DNA double-strand break.